A Medical Microcomputer Database Management System - Joyce, A. Mitchell; Naddaf-Dezfbli, A. R.; Davenport, Sandra L. H. (Methods of Information in Medicine, 1985)
The Patient Data Handler (PDH) is an interactive, microcomputer-based database management system. It is written in DEC BASIC-11 and runs on a DEC compatible LSI-11/03. The PDH is a relational database specifically designed to handle a very large number of attributes per patient. The retrieval program is capable of performing any combination of Boolean operations on the patient records. Data security is provided by several levels of password protection. The current application has 3,500 attributes associated with a research project on deaf-blind syndromes. Specific retrieval examples are shown from this database.
Keywords: Database Management System; Microcomputers; Genetic Diseases; Deafness; Blindness; Medical Records